FAKTOR RASIO C/N AWAL DAN LAJU AERASI PADA PROSES CO-COMPOSTING BAGASSE DAN BLOTONG - Andes Ismayana, Nastiti Siswi Indrasti, Suprihatin, Akhiruddin Maddu, Aris Fredy TIP (Jurnal Teknologi Industri Pertanian, 2012)
Sugar cane industry generates wastes, such as bagasse and filter cake which were still not used optimally. One of the alternative utilizations is through the co-composting process to produce compost. The objectives of the study were to utilize bagasse and filter cake from the sugar industry waste for composting and to determine the effect of aeration and C/N ratio to the process and the quality of compost. Method of composting was carried out by using the aerated static pile with two factors, i.e. aeration and C/N ratio. Aeration was given in the form of active aeration for 1 hour in the first week, of 0.4 and 1.2 l / min.kg, and C/N ratio of 30, 40, and 50 for both aerations. Co-composting process had formed mesophilic temperature with the highest at 38 oC, with a range of pH 6.0-7.5 at day 22 and then constant in the range of 6.8-8.0. C/N ratio final compost produced was 17-25, with the biggest C/N ratio decreases at the initial C/N ratio of 50, whereas the aeration rate of 1.2 l/min.kg gave bigger changes in C / N ratio.Keywords: co-composting, bagasse, blotong, aeration